Mapping Temperature Zone of Ethiopia for Binder Performance Grading System - Mahlet G. Mihretu; Habtamu M. Zelelew (Advances in Civil Engineering)
Several studies from the Strategic Highway Research Program (SHRP) have demonstrated that improving asphalt binder standards by incorporating performance-based characteristics can benefit road network administrators. This approach provides a better understanding of pavement behavior during its operational phase. Despite these findings, Ethiopia’s current asphalt binder procurement process still relies on the penetration grading system, which uses a 25°C test temperature with a 100-g loading weight. This method fails to simulate the extreme temperature and loading conditions that pavements experience. Additionally, the empirical parameters derived from this test do not fully capture the stress–strain relationships of pavement performance. This research introduces the performance grading (PG) system, a key component of SHRP’s developments, with two main objectives: (1) to develop a PG map for Ethiopia and (2) to evaluate asphalt binder performance using PG testing standards. Achieving these objectives requires two different approaches. First, the PG map was developed using 20 years of air temperature data from the National Meteorological Agency. The SHRP prediction model was applied to convert air temperature to pavement temperature, yielding a PG classification with 98% reliability. The second objective involved performing conventional and Superpave binder tests on asphalt samples collected from various ongoing projects. The PG determination test provided a generic binder classification, while the multiple stress creep recovery (MSCR) tests delivered more detailed performance data, including traffic loading capacity and maximum temperature tolerance. The results identified five major PG-grade temperature zones in Ethiopia, with PG 58-10 and PG 64-10 dominating. While the asphalt binders are suitable for most regions, projects in eastern and western Ethiopia (PG 76-10 and PG 70-10) may experience excessive rutting with current binders usage (60/70 and 40/50).